The letters of Alciphron : a unified literary work? - Biraud, Michèle,; Zucker, Arnaud, (Mnemosyne, Supplements, 2018)
In 'The Letters of Alciphron: A Unified Literary Work?', Michèle Biraud and Arnaud Zucker have gathered a dozen international contributions about the collection of letters of Alciphron, hitherto mainly studied as part of the epistolary genre at the time of the Second Sophistic or as testimony of a nostalgia for the Athens of Menander's time. The aim is to show the unity of a literary project through studies on the careful arrangement of each book (overall organization, coherent reappropriation of a culture, innovations in generic hybridization) and various elements of cohesion between the four books. For this purpose, were used as tools codicological criticism, stylistic and rhetorical examination, analysis of prosody, study of thematic treatments, uses of onomastics.